The role of advertising and its impact on consumer behavior (Asia Cell as a model) (The Peerian Journal, 2025)
This research aims to study the relationship between advertising and consumer behavior, by analyzing how advertising messages in their various forms influence purchasing decisions and individuals' attitudes toward products or services. Advertising is examined in terms of its concept, objectives, and types, in addition to reviewing its various tools and media, with a focus on how these elements can be used to influence the target audience . The research also addressed the concept of consumer behavior and the factors influencing it, whether psychological, cultural, social, or personal, and how consumers interact with advertisements within multiple media environments. The research demonstrated that advertising plays a pivotal role in stimulating desire, building impressions, and directing purchasing behavior, especially when it is carefully considered and targeted. The research concluded with an applied study that examined a real-life model (such as Asia cell) to understand the effectiveness of advertising campaigns in influencing a specific target audience. This helped derive several conclusions and recommendations that enhance the effectiveness of advertising in the market and support companies in building sustainable relationships with their consumers.